Entropy drives the insertion of ibuprofen into model membranes. Issue 38 (20th September 2018) - Rojas-Valencia, Natalia; Lans, Isaias; Manrique-Moreno, Marcela; Hadad, C. Z.; Restrepo, Albeiro
Abstract : Entropy drives the insertion of ibuprofen into cell membranes. Abstract : Understanding the migration of exogenous molecules to the interior of cell membranes is of pivotal importance to the design of new drugs and to the improvement of the capabilities of existing ones. This research dissects, from a molecular perspective, using classical molecular dynamics, the thermodynamic factors driving the insertion of ibuprofen into a model phosphatidylcholine membrane in an aqueous environment. We suggest an analysis of the insertion path that focuses on the net resulting force acting on the tertiary drug/water/membrane system; this allows us to understand the opposition that ibuprofen has to overcome as it inserts into the membrane. We provide conclusive evidence that entropy changes, arising from an increase of the number of possible microstates due to structural reorganization of the tertiary system, are the main factor driving this process. Our results allow us to unambiguously rationalize long standing conflicting experimental reports not understood up to now.